Analysis of Construction Safety Costs In Girder Erection Work On Toll Road Projects To Reduce Risks And Construction Accident Costs - Wicaksono, Aditya Daniar; Machfudiyanto, Rossy Armyn (CSID Journal of Infrastructure Development, 2026)
The construction of toll roads, as part of Indonesia’s National Strategic Projects, plays a crucial role in enhancing mobility and economic competitiveness. Girder erection work constitutes one of the most critical phases in toll road bridge construction, characterized by high safety risks due to confined workspaces, technical complexity, and suboptimal risk management practices. This study aims to analyze construction safety costs in girder erection work to reduce risks and construction accident costs. The research process includes hazard identification, effective risk control analysis, risk impact valuation, and cost-benefit analysis of safety investments. The methods employed consist of secondary data analysis, risk level assessment based on frequency and severity, and expert validation. The findings reveal that most girder erection activities are categorized as high risk, with the primary hazard being falls from height. Risk control strategies were implemented through technical measures, administrative controls, and the use of personal protective equipment (PPE). The total risk impact value was found to be approximately 25% to 38% of the girder erection work cost, while the allocated safety cost was only 1.72% to 2.57%. The cost-benefit analysis yielded a ratio of 1: 8.25, indicating significant cost savings and the economic feasibility of safety investments. These findings reinforce previous research (Ikpe et al., 2011) which confirmed the positive contribution of safety costs to accident prevention and align with OSHA’s perspective on cost savings through the implementation of safety programs. Therefore, the allocation of construction safety costs proves to provide substantial benefits in risk reduction and cost efficiency. This study contributes to the development of implementable strategies for project stakeholders to optimize the benefits of safety cost allocation in girder erection work on toll road projects.